Answer: h(x) = 2x^2-2
========================================================
Step-by-step explanation:
We shift the graph of g upward by 3 units. This means we add 3 onto g(x) like so
h(x) = g(x)+3
h(x) = (2x^2-5)+3
h(x) = 2x^2-5+3
h(x) = 2x^2-2
All points on g(x) move up by 3 units to get to a point on h(x). For instance, the y intercept (0,-5) on g(x) moves to (0,-2) on h(x).
When we say something like g(x)+3, we effectively mean y+3 to indicate an upward shift of 3 units. Recall that y = g(x) because they are both outputs.